Plasma-mediated inactivation of Pseudomonas aeruginosa biofilms grown on borosilicate surfaces under continuous culture system - Vandervoort, Kurt (2014)
Biofilms are microbial communities attached to a surface and embedded in a matrix composed of exopolysaccharides and excreted nucleic acids. Bacterial biofilms are responsible for undesirable effects such as disease, prostheses colonization, biofouling, equipment damage, and pipe plugging. Biofilms are also more resilient than free-living cells to regular sterilization methods and therefore it is indispensable to develop better ways to control and remove them. The use of gas discharge plasmas is a good alternative since plasmas contain a mixture of reactive agents well-known for their decontamination potential against free microorganisms. We have previously reported that Pseudomonas aeruginosa biofilms were inactivated after a 1-min plasma exposure. We determined that the adhesiveness and the thickness of Pseudomonas biofilms grown on borosilicate were reduced. We also reported sequential morphological changes and loss of viability upon plasma treatment. However, the studies were carried out in batch cultures. The use of a continuous culture results in a more homogenous environment ensuring reproducible biofilm growth. The aim of this work was to study plasma-mediated inactivation of P. aeruginosa biofilms grown on borosilicate in a continuous culture system. In this paper we show that biofilms grown on glass under continuous culture can be inactivated by using gas discharge plasma. Both biofilm architecture and cell culturabilty are impacted by the plasma treatment. The inactivation kinetics is similar to previously described ones and cells go through sequential changes ranging from minimal modification without loss of viability at short plasma exposure times, to major structure and viability loss at longer exposure times. We report that changes in biofilm structure leading to the loss of culturability and viability are related to a decrease of the biofilm matrix adhesiveness. To our knowledge, there has been no attempt to evaluate the inactivation/sterilization of biofilms grown in a continuous system.